Fuzzy Parameterized Intuitionistic Fuzzy Soft Sets and Their Application to a Performance-Based Value Assignment Problem - Tuğçe Aydın; Naim Cagman; Emre Sulukan (Journal of New Theory, 2019)
Soft sets have been successfully applied to many different fields to cope with uncertainties. Recently, to increase the success of the applications, these sets have been combined with other theories, such as fuzzy sets and intuitionistic fuzzy sets. In this study, we propose the concept of fuzzy parameterized intuitionistic fuzzy soft sets (fpifs-sets). We then apply these sets to a performance-based value assignment (PVA) problem. Finally, we give suggestions for further research.